Folic Acid Attenuates High-Fat Diet-Induced Osteoporosis Through the AMPK Signaling Pathway - He, Haiting; Zhang, Yaxi; Sun, Yue; Zhang, Yanwei; Xu, Jingjing; Yang, Yuzhen; Chen, Jihua (Frontiers in Cell and Developmental Biology, 2022)
Objective: Obesity caused by a high-fat diet (HFD) will expand adipose tissue and cause chronic low-grade systemic inflammation, leading to osteoporosis. Folic acid (FA) is a water-soluble vitamin that plays an essential role in regulating blood lipids and antioxidants. However, the effects and underlying mechanisms of FA in osteoporosis induced by an HFD remain poorly understood. This study aimed to investigate the effect of FA on bone health by using HFD-induced osteoporosis mice. Materials and Methods: Mice were fed a normal diet, HFD or an HFD supplemented with FA (20 μg/ml in drinking water) for 16 weeks. Throughout the 16 weeks study period, the rats were weighed once every week. GTT, ITT and lipid indexes were detected to evaluate the effects of FA on lipid metabolism in the HFD-fed mice. Morphological and structural changes of the femur and tibial bone were observed using micro-CT, HE staining and bone conversion parameters. The expression of MDA, SOD and inflammatory factors were detected to evaluate the effects of FA on oxidative stress and inflammatory response in the HFD-fed mice. Quantitative real-time PCR and Western blot (WB) were used to investigate the AMPK signaling pathway. Results: After the intervention of FA, the body fat rate of obese mice was reduced, and related metabolic disorders such as insulin resistance, hyperlipidemia, and systemic inflammation were alleviated. In correlation with those modifications, FA attenuated bone loss and improved bone microarchitecture, accompanied the number of osteoclasts and adipocytes decreased. Furthermore, FA promoted the phosphorylation of AMPK, thereby promoting the expression of Carnitine palmitoyltransferase 1 (CPT1), nuclear factor erythroid-2 related factor 2 (Nrf2) and antioxidant enzymes. Conclusion: These findings suggest that FA may modulate lipid metabolism and oxidative stress responses activating the AMPK signaling pathway, thereby alleviating HFD-induced osteoporosis. The results from our study provide experimental evidence to prevent HFD-induced osteoporosis.